Crisis and Austerity in Southern Europe: Impact on Economies and Societies - Serapioni, Mauro (2019)
This article discusses the economic and social impact of the 2008 crisis and its related austerity policy on South European countries (SEC). Damages caused by these policies includes the decrease in GDP, the increase in unemployment and precariousness, especially amongst the younger population, and the worsening of social services. SEC health systems have also been seriously affected by the crisis, with a particular impact on the most vulnerable social groups, as a result of the decrease in public health expenditure. The increase in health inequalities is another side effect of the structural adjustment programs.